An Observation-Based Study of Silver Pomfret (Trachinotus blochii) Hatchery Practices at Lombok Marine Aquaculture Center - Rahman, Ihsan Sanggar (Aquatic Life Sciences, 2024)
This observation-based study evaluates the seed production practices of Silver Pomfret (Trachinotus blochii) at the Lombok Marine Aquaculture Center (BPBL Lombok), West Nusa Tenggara, Indonesia. BPBL Lombok is a key facility for marine aquaculture, focusing on breeding species such as the star snapper in an environment with optimal water quality and well-equipped facilities. The study investigates broodstock management, including hormonal induction for spawning, and the growth and grading processes of fry at various developmental stages. Stocking densities were adjusted based on size, and water quality parameters were closely monitored to ensure the survival and growth of the fry. The study also examines the impact of feed management, gonad maturation, and water quality control on the survival rate (SR) of T. blochii fry, with the results indicating a typical SR of 50%, with optimal management. The findings contribute valuable insights for improving Silver Pomfret breeding practices and highlight the importance of sustainable aquaculture techniques for the development of marine fish farming in Indonesia.